Aaron Sinsheimer and Henry Morse Stephens on trail to Avila Beach (1910)
Aaron and Henry are accompanied by one of Sinsheimer's daughters as they travel on the trail to Avila Beach on horse drawn carriages. They are carrying fishing poles as well.